Integral Calculus Learning Using Problem Based Learning Model Assisted by Hypermedia-Based E-Book - Awaludin, Awaludin; Wibawa, Basuki; Winarsih, Murni (JPI (Jurnal Pendidikan Indonesia), 2020)
The focus of this study is the effectiveness of the Problem Based Learning (PBL) model assisted by hypermedia-based e-books on the results of integral calculus learning. The objectives of the study are (1) to describe the students’ learning outcomes of integral calculus which are taught through problem-based learning model with the help of a hypermedia-based e-book, and (2) to find out the effectiveness of the Problem Based Learning model with the help of a Hypermedia-Based e-book on integral calculus learning outcomes. This research employed an experiment with a posttest only control design. The study population was all students from the Department of Mathematics Education, Halu Oleo University in the 2017-2018 academic year. The study sample consisted of 60 students distributed equally in two classes namely the experimental class (30) and the control class (30). The Problem Based Learning model with the help of a hypermedia-based e-book was applied in the experimental class while the traditional learning model with the help of printed teaching materials was applied in the control class. The PBL learning model steps consist of (1) presenting contextual problems, (2) forming cooperative groups, (3) analyzing problems cooperatively, (4) presenting the results of group discussions, (5) reflections. Data were collected using the test of integral calculus learning. Then the data were analyzed descriptively and inferentially. The descriptive analysis included the mean value, variance, and standard deviation, while the inferential analysis included the data normality test, the data homogeneity test, and the average difference test. The results showed that the students' integral calculus learning outcomes taught with Problem Based Learning model was categorized well, and the PBL learning model effectively improved the integral calculus learning outcomes.